2020
DOI: 10.1038/s41598-020-63213-2
|View full text |Cite
|
Sign up to set email alerts
|

Influence of Chronic Ethanol Consumption on Apoptosis and Autophagy Following Transient Focal Cerebral Ischemia in Male Mice

Abstract: Background Inflammation and apoptosis are two key elements involved in cerebral ischemia/reperfusion (I/R) injury. Ethanol is one of the most commonly and regularly used chemical substances. We determined the influences of chronic ethanol consumption on inflammation and apoptosis following transient focal cerebral ischemia. Methods Male C57/BL6J mice were divided into 6 groups and gavage fed with 0.175, 0.35, 0.7, 1.4, 2.8 g/kg/d ethanol or volume‐matched water once a day for eight weeks. Cerebral I/R injury, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
26
0
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 21 publications
(31 citation statements)
references
References 41 publications
3
26
0
2
Order By: Relevance
“…Several recent studies show that in the adult, there are indications that ethanol could have positive effects particularly for the traumatized brain [3][4][5][6][7][8][9][10]50]. Some of the mechanisms proposed to mediate this positive effect of low concentrations of ethanol are to suppress apoptosis and inflammation.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Several recent studies show that in the adult, there are indications that ethanol could have positive effects particularly for the traumatized brain [3][4][5][6][7][8][9][10]50]. Some of the mechanisms proposed to mediate this positive effect of low concentrations of ethanol are to suppress apoptosis and inflammation.…”
Section: Discussionmentioning
confidence: 99%
“…Strikingly, these studies found a strong correlation between low intake and lower risk and severity of post-ischemic injury. Both effects in apoptosis and inflammation are proposed to be involved in the mechanism in rodents [9,10].…”
Section: Introductionmentioning
confidence: 99%
“…Our recent studies found that 8-week gavage feeding with 0.7 g/kg/day ethanol prior to the ischemia significantly decreased infarct size and neurological deficits in a mouse model of transient focal cerebral ischemia [ 21 , 22 ]. The peak blood alcohol concentration was about 9 mM [ 21 ].…”
Section: Discussionmentioning
confidence: 99%
“…To measure the infarct size, sections from eight levels (between 2.9 mm rostral and 4.9 mm caudal to bregma) were selected for Nissl staining as described previously [ 22 ]. The sections were incubated in 0.01% cresyl violet acetate (Sigma, St. Louis, MO, USA) solution for 14 min at 60 °C, rinsed in distilled water, dehydrated in ethanol, cleaned in xylene, and covered with xylene-a based mounting media (VWR).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation